Establishment of Infrastructure for Electric Vehicles in Azerbaijan (Problems and Prospects) - Hamidov, M.M.; Manafov, Q.C. (Herald of Azerbaijan Engineering Academy, 2025)
The increase in the use of electric vehicles dictates the holding of advertising events, and it is necessary to create the appropriate infrastructure for their continuous operation. For this purpose, recommendations are proposed for the organization of suitable work, the placement of electric charging stations with prospective development.